A one-year, postfire record of element deposition and cycling in the Kogelberg sandstone fynbos mountain ecosystem of the Western Cape, South Africa by Eugene W. Bergh. - Bergh, Eugene W (Department of Geological Sciences, 2014)
Includes abstract.